ANALISIS PENYABAB KERUSAKAN MESIN DENGAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DI PT. SULFINDO ADIUSAHA - Safitri, Salsabila; Kusumawati, Aulia; Amanda Putra, Levi; Ramayanti, Gina (Prodi Teknik Industri, Fakultas Teknik, 2024)
PT Sulfindo Adiusaha is a chemical company focused on operational efficiency and quality. The main issue faced is frequent machine breakdowns, particularly mechanical seal leakage, which disrupts production processes. This study aims to analyze the causes of damage using the Failure Mode and Effect Analysis (FMEA) method to determine repair priorities. The analysis results show that mechanical seal leakage has the highest Risk Priority Number (RPN) of 504, making it the top repair priority. The main causes of damage include human factors, maintenance methods, materials, and machine wear. Recommendations for improvement include operator training, replacing components with heat-resistant materials, and structured periodic maintenance. These steps are expected to enhance productivity and reduce downtime risks.